The Unusual Prominence of the Burial Shroud in the Deponitur Christi Corpus E Curce from the Adnotationes et Meditationes in Evangelia - (:unkn) unknown (My University, 2023)
In this thesis, I analyze the iconography and the accompanied text of Hieronymus Wiericx’s Deponitur Christi corpus e cruce (Christ’s body is taken down from the cross; Image 132, Chapter 105; hereafter referred to as the Deposition) from Adnotationes et meditationes in Evangelia (Annotations and Meditations on the Gospels; hereafter referred to as Adnotationes et meditationes) by Jerome Nadal, originally published in 1595. I examine the unusual prominence of the burial shroud depicted behind Christ whereas in previous sixteenth-century deposition imagery, the burial shroud was either omitted or not given such prominence. Scholars in recent decades have devoted significant attention to the Adnotationes et meditationes and a number of its illustrations, but they have yet to explore in detail the Deposition and the emphasis placed on the shroud by the engraving’s iconography and in the biblical passages, annotations, and meditation that accompany the image in Nadal’s book. I focus on the significance of the burial shroud in relation to the Council of Trent’s decree concerning relics and the renewed importance at the time of the Holy Shroud of Turin. I will likewise compare the shroud in Wierix’s Deposition to other post-Tridentine images of the theme, among them Peter Paul Rubens’ Descent from the Cross (1612). The iconographical study will expand the research on the engravings and text of the Adnotationes et meditationes along with relics and their significance to Christian theology and the art historical field.
Keywords: Deposition; Engraving; Jesuit; Meditation; Wierix